I undervalue you but I need you: the dissociation of attitude and memory toward in-group members. - Ke Zhao (Public Library of Science (PLoS), 2012)
In the present study, the in-group bias or in-group derogation among Mainland Chinese was investigated through a rating task and a recognition test. In two experiments,participants from two universities with similar ranks rated novel faces or names and then had a recognition test. Half of the faces or names were labeled as participants' own university and the other half were labeled as their counterpart. Results showed that, for either faces or names, rating scores for out-group members were consistently higher than those for in-group members, whereas the recognition accuracy showed just the opposite. These results indicated that the attitude and memory for group-relevant information might be dissociated among Mainland Chinese.